Upaya Pengendalian Covid-19 Melalui Layanan Telemedicine Perspektif Permenkes Nomor 20 Tahun 2019 - Ridwan (As-Shahifah : Journal of Constitutional Law and Governance, 2021)
This research is entitled "Efforts to control COVID-19 through Telemedicine Services Permenkes Permenkes Number 20 of 2019". The formulation of the problems that will be raised in this study are: first, how is the effectiveness of implementing telemedicine services in an effort to control the COVID-19 virus in Indonesia. Second, how does it affect the trend of the declining rate index for COVID-19 cases in Indonesia. And third, how is the Minister of Health number 20 of 2019 in providing regulations on the implementation of telemedicine services for isoman patients. In this study, a normative juridical approach was used, with research specifications that were descriptive analysis. The data used is secondary data obtained through literature study, and then analyzed qualitatively. The results of the study can be concluded that: first, that the implementation of telemedicine services for controlling cases of the COVID-19 virus in Indonesia is very effective. Telemedicine comes from the Greek, namely tele which means far and medical which means health services by health workers. According to the provisions in the Regulation of the Minister of Health of the Republic of Indonesia Number 20 of 2019 concerning the Implementation of Telemedicine Services Between Health Service Facilities Telemedicine is the provision of long-distance health services by health professionals using information and communication technology, including the exchange of information on diagnosis, treatment, prevention of disease and injury, research and evaluation, and continuing education of health care providers for the benefit of improving individual and community health.